Ongoing symptoms after eradication of Helicobacter pylori: Psychiatric disorders may accompany! - Hakan Ümit ÜNAL,; Ebru Akın,; İsmail AYDIN,; Murat Korkmaz,; Sevgi ÖZEL,; Haldun Selçuk,; Uğur Yılmaz, (Turkish Journal of Gastroenterology, 2019)
-